Differential bacteriology of extradural, subdural, and intra-parenchymal suppuration at Chris Hani Baragwanath Academic Hospital (CHBAH): a 5-year review of records - Jaiyeola, O.M (My University, 2020)
This study reports on 365 patients who presented to Chris Hani Baragwanath Academic Hospital between July 2013 and June 2018, with intracranial suppuration of which 240 patients had surgical drainage. The study aimed at determining differences in the types of bacterial isolates and their respective antimicrobial susceptibility profiles from Extradural Empyema (EDE), Subdural Empyema (SDE), and Brain Abscess (BA). EDE accounted for 37 (15.4%) of the intracranial collections; SDE group were 85 (35.4%); while BA accounted for 118 (49.2%). One hundred and thirty (54.2%) of the patients who had surgical drainage had positive bacterial cultures from an intracranial collection while the remaining 110 (45.8%) had negative cultures. Males contributed to the majority of the patients with intracranial suppuration; 172 males (71.7%) and 68 females (28.3%), respectively. This was attributed to a larger number of male patients with intracranial infections as a result of trauma. A total of 167 bacterial isolates were cultured in 140 patients as some specimens grew multiple organisms. Twenty nine organisms were cultured from EDE, 62 from SDE and 76 from BA. Gram positive bacteria were the most common organisms cultured, comprising 53% of total bacterial isolates. Fifty nine percent of EDE (17 out of 29) and 68% SDE (42 out of 62) isolates were Gram positive organisms. BA cultured mostly Gram negative organisms (43%) followed by Gram positive isolates which made up 38% (29 out of 76). Some patients with Human Immunodeficiency Virus (HIV)-related BA were found to have opportunistic infections such as Tuberculosis and Nocardia. Overall, Staphylococcal and Streptococcal species were the most common organisms cultured. EDE, SDE, and BA had a frequency of Staphylococcal culture of 76% (13/17), 33% (14/42), and 52% (15/29), respectively. EDE, SDE, and BA had a frequency of Streptococcal culture of 12% (2/17), 52% (22/42), and 38% (11/29) respectively. The antimicrobial sensitivities of the specific organisms isolated were similar irrespective of the cavity (EDE, SDH, or BA) from which they were obtained. The default empiric treatment of ICS was a broad spectrum Cephalosporin (covering GPB and GNB) and anti-anaerobic agent (Metronidazole). Based on the findings of this study, it is recommended that empiric antimicrobial choice should be based on source of primary infection. BA resulting from different sources of infection have higher incidence of GNB and may require the use of Carbapenems if resistant to commonly used antibiotics. Post neuro-surgical nosocomial infections have higher incidence of Staphylococcal and Extended Spectrum Beta Lactamase (ESBL) Gram negative infections, hence, may require Vancomycin and a Carbapenem empirically. Patients with associated immunodeficiency may be suspected of having opportunistic infections, e.g. Tuberculosis or Nocardia if other sources of infections were ruled out and radiologic imaging are in support of such infections.
A research report submitted in fulfilment of the requirement for the degree of Master of Medicine in Neurosurgery to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020